Application of Probit Analysis in the Decision of Youths to Participate in Vegetable Production - Nsikak-Abasi Etim; Dorothy Thompson (Newinera Publisher, 2020)
Youths are successor farming generation and therefore the future of food security. At present, they constitute about 60% of Nigeria’s population and have over the years contributed significantly to national development. Unfortunately, the present environment makes it difficult to explore their full potentials in production through participation in agriculture. The ageing smallholder farmers are less likely to increase capacity needed to sustainably expand agricultural production. There is therefore a pressing need to engage the youth in ways that they can see a promising future in agriculture as well as influence them to build capacity through effective involvement in agricultural production. Several factors however, have continued to hinder capacity building and effective participation of youths in vegetable farming. An empirical study was conducted to estimate the factors affecting the willingness of youth to participate in small scale waterleaf production. The representative waterleaf producers were selected using the multi stage sampling procedures.With the aid of questionnaire, primary data were obtained from 100 farmers. Univariate probit regression model was used to analyze the data. Results of analysis indicated that the most critical factors affecting the participation of youths in waterleaf production were age, educational qualification, size of household members, and farm income. Results indicated that youths who have acquired some form of education were more willing to be involved in waterleaf production. Findings further indicated that youth in families with higher income from farming activities were more willing to participate in waterleaf production.